Studi rantai nilai tepung sagu di Kota Kendari - Dwi Abriani Putri Utami; Ine Fausayana; Budiyanto Budiyanto (Jurnal Sosio Agribisnis, 2023)
Study of the sago starch value chain can help determine the sago value chain and the added value of sago processing, so that it can be an effort to maintain the sustainability of the sago industry. The study was carried out in April 2022–January 2023 in Kendari City, Southeast Sulawesi. The study population consists of 3 (three) categories, namely farmers, sago flour processors, and traders. Sample determination was carried out using the census method. The variables observed are input prices, production costs, output prices, added value, marketing volume, marketing costs. The analysis used is value chain analysis, added value, and marketing efficiency. The study results show that the sago starch value chain in Kendari City consists of 3 (three) segments, namely the upstream segment which includes raw material suppliers, namely farmers, the middle segment which has added value processes, and finally the downstream segment. The main actors in this value chain consist of farmers, home industries and distributors. The added value carried out in the process of processing sago stems into sago flour is IDR. 17,461.89 per kg obtained at Kube Maju Bersama, higher than the added value at UD. Konawe Songgi (Rp. 17,320.8 per kg) and UD. Dani Putra (Rp. 17,261.56 per kg). All sago starch processing industries in Kendari City are said to have efficient marketing, as indicated by a marketing efficiency value of < 33 percent. Keywords: value chain; value-added; efficiency